Reflecting on Dunbar’s numbers: Individual differences in energy allocation to personal relationships - Wenbo Li; David S. Lee; Jonathan L. Stahl; Joseph Bayer (PLoS ONE, 2025)
Past studies have investigated the variability in how people engage with their personal networks, yet less is known about how people perceive their energy allocation to different ties. Drawing on an online survey sample (N =  906), we tested whether subjective perceptions of energy allocation conform to so-called Dunbar’s Number(s). In addition, we evaluated the predictive roles of Big Five personality traits and self-esteem while controlling for differences in network structure. Results revealed significant heterogeneity in perceived energy allocation to different layers of personal networks (i.e., inner 5 vs. middle 15 vs. outer 150 relationships). In contrast to expectations, extraversion was not associated with perceived energy allocation, whereas self-esteem was associated with greater energy allocation to the middle (vs. inner) network layer. Our findings add to our knowledge of how people perceive relationship maintenance across their personal networks, along with the links to key psychological traits. More broadly, the findings suggest that more attention should be paid to psychological implications of the middle layer of personal networks. To conclude, we discuss the importance of studying individual differences in how people prioritize – and reflect on – different relationships in their networks.